The contemporary distribution of Trypanosoma cruzi infection in humans, alternative hosts and vectors. - Browne, A; Guerra, C; Alves, R; da Costa, V; Wilson, A; Pigott, D; Hay, S; Lindsay, S; Golding, N; Moyes, C (Scientific Data, 2017)
Chagas is a potentially fatal chronic disease affecting large numbers of people across the Americas and exported throughout the world through human population movement. It is caused by the Trypanosoma cruzi parasite, which is transmitted by triatomine vectors to humans and a wide range of alternative host species. The database described here was compiled to allow the risk of vectorial transmission to humans to be mapped using geospatial models. The database collates all available records, published since 2003, for prevalence and occurrence of infection in humans, vectors and alternative hosts, and links each record to a defined time and location. A total of 16,802 records of infection have been extracted from the published literature and unpublished sources. The resulting database can be used to improve our understanding of the geographic variation in vector infection prevalence and to estimate the risk of vectorial transmission of T. cruzi to humans.